Cultivating Cross-Cultural Competencies for Heritage Tourism Encounters in Jambi: An HRD Framework for Frontline Staff Development - Darmawanto; Panji Ulum; Feri Antoni; Sasmita Rusnaini; Hamirul (Enigma Institute, 2024)
Heritage tourism is vital for Jambi's economy and cultural preservation, attracting increasingly diverse visitors. Effective cross-cultural encounters, mediated by frontline staff, are crucial for positive visitor experiences and sustainable tourism. However, staff often lack specific Cross-Cultural Competencies (CCC) needed for the unique Jambi heritage context, potentially leading to service failures. This study aimed to develop and validate a context-specific Human Resource Development (HRD) framework to cultivate CCC among frontline staff at Jambi heritage sites. A sequential exploratory mixed-methods design was employed. Phase 1 involved qualitative exploration (n=18 staff focus groups, n=6 manager interviews) at major Jambi heritage sites to identify required CCC dimensions. Phase 2 involved a quantitative survey (n=125 frontline staff) using a developed instrument (CCCI-HSJ) to assess baseline CCC levels. Phase 3 comprised developing the HRD framework based on findings, validating it via an expert panel (n=9), and pilot testing the framework through a training intervention (n=22 staff) with pre/post-assessment. Five core CCC dimensions specific to the Jambi heritage context were identified: Cultural Self-Awareness & Reflection, Jambi-Specific Cultural Knowledge & Sensitivity, Intercultural Communication Adaptability, Intercultural Relationship Building & Empathy, and Coping with Intercultural Ambiguity & Stress. Baseline assessment revealed moderate overall CCC levels, with specific weaknesses in communication adaptability and handling ambiguity. The developed HRD framework received strong validation from experts regarding relevance and comprehensiveness. The pilot training resulted in statistically significant improvements (p < 0.001) in participants' overall CCC scores. Frontline staff in Jambi's heritage tourism sector require targeted development of specific CCC dimensions. The validated HRD framework provides a structured, contextually relevant approach to enhance these competencies, contributing to improved service quality and more meaningful visitor experiences. Implementation of this framework is recommended for sustainable heritage tourism development in Jambi.